The Influence of the Problem-Based Learning Model Assisted by Liveworksheets on the Critical Thinking Skills of 11th-grade Students in Biology Subjects - Raicha Oktafiani; Nukhbatul Bidayati Haka; Aryani Dwi Kesumawardani; Novi Eka Lestari (WISE Pendidikan Indonesia, 2024)
Education equips individuals with intellectual intelligence, good attitudes, and skills that benefit both themselves and their surroundings in the future. The problem-based learning model encourages students to develop critical thinking skills. In biology learning, a shift is necessary from teacher-centered instruction to student-centered learning. This study aims to examine the influence of the problem-based learning model assisted by Liveworksheets on the respiratory system material. Liveworksheets introduce an innovative and engaging approach to problem-solving through features like video and audio clips, designed to maximize students' critical thinking skills. This quantitative research employed a quasi-experimental method. The population consisted of all 105 11th-grade science students at SMA N 08 Bandar Lampung, distributed across four classes. The sample was selected using cluster random sampling, with class XI IPA 2 as the control group and class XI IPA 4 as the experimental group. Data were analyzed using an Independent Sample T-Test to test the hypotheses. The normality test was conducted using the Shapiro-Wilk test to determine whether the data followed a normal distribution, while the homogeneity of variance test assessed the uniformity of data variances. The results revealed a significant influence of the problem-based learning model assisted by Liveworksheets on the critical thinking skills of 11th-grade students studying the respiratory system at SMA N 08 Bandar Lampung. This was indicated by a significance value of 0.000 (< 0.05), leading to the rejection of H0 and acceptance of H1. These findings demonstrate the effectiveness of the problem-based learning model assisted by Liveworksheets in enhancing students' critical thinking abilities.